2022
DOI: 10.1186/s12888-022-04373-5
|View full text |Cite
|
Sign up to set email alerts
|

Sudden gamer death: non-violent death cases linked to playing video games

Abstract: Background and aims Internet gaming disorder (IGD) is an emerging problem. Rarely, media reports about people, who have died during playing video games, but thus far no systematic, scientific study is available about the topic. We investigated such cases, looking for common characteristics, connection between gaming and death, and the possible reasons leading to death. Methods Cases were collected through internet search with general keywords, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…One study specifically highlighted the exacerbation of preexisting mental disorders, linking ADHD to disruptive mood dysregulation disorder (DMDD) in the presence of internet gaming problems [23]. Additionally, another study revealed the potential risks associated with prolonged video game-playing sessions, leading to mortality [24]. Lastly, a few studies reported some positive effects on academic performance, as well as mental and social well-being [9,15,17,[25][26][27].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study specifically highlighted the exacerbation of preexisting mental disorders, linking ADHD to disruptive mood dysregulation disorder (DMDD) in the presence of internet gaming problems [23]. Additionally, another study revealed the potential risks associated with prolonged video game-playing sessions, leading to mortality [24]. Lastly, a few studies reported some positive effects on academic performance, as well as mental and social well-being [9,15,17,[25][26][27].…”
Section: Resultsmentioning
confidence: 99%
“…There have also been incidents of violence and suicides where video games were cited as the main motivating factor. A study conducted by Kuperczko et al aimed to identify cases reported in online newspapers, blogs, and video portals where a gamer's death was directly attributed to playing the game (excluding suicides or homicides driven by frustration, anger, impulse, retaliation, or carelessness) [ 24 ]. Most of the 24 victims identified were from internet cafes in Southeast Asia.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly-cited displaced activities include gaming leading to lost sleep (Guo et al, 2022), lower performance at work or school (Drummond and Sauer, 2020), or failure to maintain social relationships (Kowert et al, 2014). In the most extreme examples, gaming can displace all other life activities to the point of player death after multiple days of uninterrupted gaming (Kuperczko et al, 2022).…”
Section: Displacementmentioning
confidence: 99%
“…However, this focus on quality should not be understood as an indication that quantity of gameplay never affects mental health. Evidence from case studies demonstrates that excessive time spent gaming can come at a severe cost to some players-with the most extreme examples involving player death after multiple days of uninterrupted gaming (Kuperczko et al, 2022). More typical examples involve time spent gaming leading to lost sleep (Guo et al, 2022), lower performance at work or school performance (Drummond and Sauer, 2020), or the inability to maintain social relationships (Kowert et al, 2014).…”
Section: Background 21 Empirical Desideratamentioning
confidence: 99%